Biased probability judgment: evidence of incidence and relationship to economic outcomes from a representative sample - Thomas Dohmen; Armin Falk; David Huffman; Felix Marklein; Uwe Sunde (Institute for the Study of Labor (IZA), 2009)
Many economic decisions involve a substantial amount of uncertainty, and therefore crucially depend on how individuals process probabilistic information. In this paper, we investigate the capability for probability judgment in a representative sample of the German population. Our results show that almost a third of the respondents exhibits systematically biased perceptions of probability. The findings also indicate that the observed biases are related to individual economic outcomes, which suggests potential policy relevance of our findings.
urn:nbn:de:101:1-2009060824
Keywords: C90; D00; D10; D80; D81; H00; 330; Bounded rationality; probability judgment; gambler's fallacy; hot hand fallacy; representative design; long-term unemployment; financial decision making; Beschränkte Rationalität; Entscheidung bei Unsicherheit; Test; Langzeitarbeitslosigkeit; Konsumentenverhalten; Deutschland